Efficacy and Safety of Phytosomal Curcumin in Non-Alcoholic Fatty Liver Disease: A Randomized Controlled Trial - Panahi, Yunes; Kianpour, Parisa; Mohtashami, Reza; Jafari, Ramezan; Simental-Mendía, Luis E.; Sahebkar, Amirhossein (Drug Research, 2017)
Non-alcoholic fatty liver disease (NAFLD) is a common liver disease characterized by excess lipid deposition in the hepatic tissue and subsequent oxidative and inflammatory damage. Curcumin is a dietary polyphenol with lipid-modifying, antioxidant and anti-inflammatory properties. This study aimed to evaluate the efficacy and safety of supplementation with phytosomal curcumin in subjects with NAFLD.Patients diagnosed with NAFLD (grades 1–3 according to liver ultrasonography) were randomly assigned to the curcumin (phytosomal form; 1 000 mg/day in 2 divided doses) (n=50) or placebo group (n=52) for a period of 8 weeks. All patients received dietary and lifestyle advises before the start of trial. Anthropometric measurements, hepatic enzymes, and liver ultrasonography were assessed at baseline and after 8 weeks of follow-up.87 subjects (n=44 and 43 in the curcumin and control group, respectively) completed the trial. Supplementation with curcumin was associated with a reduction in body mass index (−0.99±1.25 vs.  − 0.15±1.31 in the curcumin and placebo groups, respectively; p=0.003) and waist circumference (−1.74±2.58 vs. −0.23±3.49 in the curcumin and placebo groups, respectively; p=0.024). Ultrasonographic findings were improved in 75.0% of subjects in the curcumin group, while the rate of improvement in the control group was 4.7% (p<0.001). Serum levels of aspartate aminotransferase and alanine aminotransferase were reduced by the end of trial in the curcumin group (p<0.001) but elevated in the control group (p<0.001). Curcumin was safe and well tolerated during the course of trial.Short-term supplementation with curcumin improves liver fat and transaminase levels in patients with NAFLD.
Keywords: curcuminoids; randomized controlled trial; non-alcoholic fatty liver disease; liver; steatohepatitis